PARTISIPASI TOKOH MASYARAKAT MENANGGULANGI PENYALAHGUNAAN NARKOBA DI KELURAHAN RAPPANG - Indragunawan JS; Barisan Barisan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the participation of community leaders in overcoming drug abuse in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency. The data collection techniques using observation, questionnaires, library research (library research). The population in this study was 58 people with a total sample of 58 people, the data processing technique used a frequency table with a Likert scale and analysis using SPSS 21. The results of this study indicate that for the participation of community leaders in overcoming drug abuse in Rappang Village, Panca District Rijang Sidenreng Rappang Regency obtained an average percentage result, which is 68.13%, in the good category. Based on the output of SPSS 21, it is known that the R value is 0.052, then automatically the R square value is 0.003, this means that there is an influence of Variable (X) Community Leaders' participation on (Y) Combating Drug Abuse by 52%.